MANAJEMEN STRATEGIK DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI PONDOK PESANTREN SYEKH BURHANUDDIN KUNTU KECAMATAN KAMPAR KIRI - Hamsyi Yamaidi; Idris Idris; Khairil Anwar (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2020)
This study aims to determine the application of strategic management at the stage of environmental observation and analysis, strategy formulation, strategy implementation and evaluation as well as control in the development of education in the Islamic boarding school of Sheikh Burhanuddin Kuntu, Kampar Kiri District, Kampar Regency. This research is field research with a qualitative research approach—data collection techniques: observation, interview and documentation. The research informants consisted of the leaders of the Islamic Boarding School, Head of Madrasah Tsanawiyah (al-Wustha), Head of Madrasah Aliyah (al-Ulya), Deputy Head of Madrasah Aliyah (al-Ulya) Curriculum, Student Affairs, Facilities and Infrastructure and Public Relations. Data analysis techniques: deductive, inductive and comparative. The results of his research are strategic management in the development of Islamic education at the stage of environmental observation and analysis in the Islamic Boarding School of Sheikh Burhanuddin Kuntu, Kampar Kiri District, Kampar Regency, including: observation and analysis of the external environment (geographical, religious, social, cultural and economic), and observation and internal environmental analysis (Human Resources / leadership, managers, teachers and staff), students / students, sources of funds, facilities and infrastructure), Then2 the application of strategic management in the development of Islamic education at the stage of strategy formulation at Syekh Burhanuddin Kuntu Islamic Boarding School, including: formulate and determine the vision, mission and objectives, and formulate and determine the strategy, direction and policy, furthermore the application of strategic management in the development of Islamic education at the implementation stage of the strategy at Syekh Burhanuddin Kuntu Islamic Boarding School, including: implementing an education system, curriculum, schedule of learning activities, culture learning, learning methods, and finally the application of strategic management in the development of Islamic education at the evaluation and control stages (control strategy) at the Islamic Boarding School of Shaykh Burhanuddin Kuntu, including: applying regulations, etiquette and ethics of students / students, implementing regulations, etiquette and ustadz ethics / teacher, conduct communication and coordination meetings (briefings), prepare monthly reports, and prepare annual reports.